The work of seamstresses in the rural area of Pernambuco - Milanês, Renata (Universidade Federal Rural do Rio de Janeiro, 2020)
The present article aims to analyze the social relations of work and gender, through the insertion of the peasant women in clothing production in the Textile Pole of Pernambuco. Privileging rural households, the text seeks to offer an anthropological analysis with an ethnographic report, describing the individual or collective actions and the values or expectations of the interviewed. The text connects a discussion that will consider: the learning of sewing, the consequences of outsourcing, the long working hours, the relationship with the “bosses”, the reproductive domestic work, the productive homework, and financial independence. The article reveals that, although sewing has become an essential source of income for peasant women, the female entry into the labor market was followed by precariousness, making women the most affected by the informality and flexibility processes that have been occurring in the region.